2009
DOI: 10.1590/s0100-204x2009000500002
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição de solutos orgânicos e inorgânicos no ajustamento osmótico de pinhão-manso submetido à salinidade

Abstract: Resumo − O objetivo deste trabalho foi avaliar a acumulação de solutos orgânicos e inorgânicos e suas contribuições para o ajustamento osmótico de folhas de pinhão-manso (Jatropha curcas L.) submetido à salinidade. O experimento foi conduzido em delineamento experimental inteiramente casualizado, com cinco tratamentos (0, 25, 50, 75 e 100 mmol L -1 de NaCl) e quatro repetições. As plantas foram cultivadas hidroponicamente em casa de vegetação, em condições controladas de fotoperíodo (12 horas), temperatura (mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 17 publications
(17 reference statements)
1
26
1
20
Order By: Relevance
“…These results indicate that the planting density may be used as a strategy to mitigate the effect of salinity of irrigation water in the production of sunflower per unit of cultivated area. SILVA et al (2009), when studying the performance of sunflower hybrids in reduced spacing, found that the increase of planting density provided a higher achene yield and number of seeds for each chapter.…”
Section: Water Consumption (Ml)mentioning
confidence: 99%
“…These results indicate that the planting density may be used as a strategy to mitigate the effect of salinity of irrigation water in the production of sunflower per unit of cultivated area. SILVA et al (2009), when studying the performance of sunflower hybrids in reduced spacing, found that the increase of planting density provided a higher achene yield and number of seeds for each chapter.…”
Section: Water Consumption (Ml)mentioning
confidence: 99%
“…Na verdade, reduções e/ou inibições constatadas no crescimento dos vegetais, à medida que eram submetidas à salinidade, são atribuídas ao efeito osmótico, à toxicidade pela absorção excessiva dos íons Na + e Cl -e ao desequilíbrio nutricional causado pelos distúrbios na absorção dos nutrientes essenciais (Silva et al, 2009a;2009b).…”
Section: Massa Seca Total E Transpiraçãounclassified
“…A redução tem sido apontada com uma resposta comum em plantas submetidas ao estresse salino, podendo estar relacionada ao antagonismo entre Na + e K + durante o processo de absorção (Silva et al, 2009a;2009b;2010), enquanto o acúmulo pode estar associado à redução na translocação desse íon em função da menor demanda para o crescimento das plantas sob condições de estresse . Na realidade, alguns autores têm observado a existência de múltiplos sistemas de absorção com diferentes seletividades para Na + e K + o que pode refletir a necessidade da planta para coordenar o influxo desses cátions (Schachtman & Liu, 1999).…”
Section: Massa Seca Total E Transpiraçãounclassified
“…The succulent stem of J. Curcas plants works as a water buffer, supplying the leaves under reduced water availability (Matos et al, 2014b). Moreover, J. curcas plants absorb NaCl from saline solutions and use Na + and Cl -to accomplish osmotic adjustment and continue absorbing water (Da Silva et al, 2009). Lower plant height under nitrogen deficiency is due to the importance of this nutrient to a vigorous vegetative stage.…”
Section: Discussionmentioning
confidence: 99%